Eksistensi Perbankan Syariah Dalam Menyongsong Era Digitalisasi - Sultan Hasanudin; Salsabila Firdaus; Dita Khoirunjannah (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
Islamic banking is a financial institution whose implementation adheres to Islamic law which is guided by the Al-Qur`an, Hadith, Ijma`, and Qiyas. Islamic banks appeared in Indonesia around the 1990s with the establishment of Bank Muamalat Indonesia without being based on applicable laws. The development of Islamic banks cannot be separated from the digital era in which technological advances are very rapid marked by the existence of: Mobile Banking, Internet Banking, SMS Banking and Telephone Banking which are easy, comfortable and safe to use, therefore in this digitalization era it is necessary to increase public perception Indonesia towards Islamic Banks by carrying out strategic efforts related to promotion and education that can touch the religious aspects of society, so that they are able to change their attitudes and paradigms for the better and are interested in Islamic financial products.